Cross-Cultural Imagination: Survival and Harmony in Nalo Hopkinson's Brown Girl in the Ring - Mushtaq Abdulhaleem Mohammed Fattah; Ola Ahmed AL- Ajeeli (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2025)
This paper analyzes Hopkinson’s Brown Girl in the Ring (1998) through Harris’s (1983) concept of cross-cultural imagination, which envisions cultural hybridity as a path to healing and coexisting instead of effacement. By focusing on the novel's protagonist, Ti-Jeanne, the paper examines how spirituality and Caribbean mythology guide her in reconnecting with her Afro-Caribbean heritage within a dystopian Toronto setting. Through Harris’s (1983) lens, Ti-Jeanne’s identity conflict is resolved by embracing both cultures as a means to empower herself and her community. The paper examines whether one can coexist harmoniously with a new culture or if abandoning one's background is the only path to adaptation. Ultimately, the novel suggests that exploring diverse cultures is not just an academic exercise but a transformative process—one that fosters healing, reshapes societies, and cultivates mutual respect.